Impact of Learning Approaches on Achievement of Pupil Teachers in Relation to their Academic Streams at Different Levels of Intelligence - Dr Meena, (INDIAN EDUCATIONAL REVIEW, 2012)
The present study was an effort to examine how interaction between Learning Approaches (DA/SA) and Academic Streams (Arts/Science) affected the academic learning outcomes of 200 pupil teachers at their different levels of intelligence i.e., high, average and low. The obtained data was analysed with the help of 2-way ANOVA. The major findings of the study were: (i) Pupil teachers under Arts and Science group yielded significant differences in mean scores at average level of intelligence. (ii) Academic streams (Arts/Science) and Learning Approaches (DA/SA) interacted significantly with regard to mean scores at average and low level of intelligence.